(untitled) (Computer systems and information technologies, 2023)
The paper analyses the problems of maintaining software quality, namely, usability testing as a direction of ensuring this quality, analyses publications that consider the methods of electro-oculography, electro-retinography, mouse-tracking, eye-tracking, etc. and proves that the issue of improving the quality of software products largely depends on the effectiveness of usability testing. The study is based on the analysis of traditional software testing methods and tools and the proposal of mouse-tracking and eye-tracking technologies as an alternative solution to the problem. Criteria and metrics for assessing the usability of web applications were identified, an analytical approach was used as a methodological basis, which involves a comprehensive consideration of the research object, methods of comparative analysis and classification were used to obtain data, the results were processed using standard statistical methods, and the necessity and importance of usability testing of websites was assessed. The article considers generally accepted rules and recommendations in the field of usability testing, analyses quantitative and qualitative methods of usability testing evaluation, for a more detailed study of the subject of research the ergonomic interaction of a user with an information system, namely with a web resource, studies the main categories of users depending on a number of indicators, and pays special attention to establishing quality assessment criteria based on existing standards of recommendations. the article reviews the process of usability testing of information system interfaces, its analysis and evaluation, analyses the methods of electro-oculography and electro-retinography, mouse-tracking and eye-tracking technologies, and concludes that the use of eye-tracking technology will allow collecting and systematising quantitative and qualitative data on user interaction with the system and will make it possible to optimise the process of usability testing by reducing the time of its implementation. The prerequisites for conducting an experimental study of theoretical results using eye-tracking technologies have been created.